The inevitability of teaching writing: An interview with Charles Bazerman - Waigandt, Diana Mónica; Bazerman, Charles (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
In this contribution we firstly refer to the actions that have been taken in the Argentinean state higher education system to foster the development of academic literacy, and that have paved the way for the consolidation of a field of action and thought that has gradually situated academic reading and writing at the center of the learning process in academic contexts. Secondly, we present an interview with Charles Bazerman that was carried out during his visit to the Universidad Nacional de Entre Ríos in 2014. Dr. Bazerman refers to the Writing Across the Curriculum (WAC) movement as a powerful approach that addresses writing development from all the disciplines, to the role of genre and to how technology is changing the way we teach writing.